A Cross-Sectional Study of the Perception of Individualized Nursing Care Among Nurses in Acute Medical and Perioperative Settings - Ramos, Ana (2024)
Funding Information: The present publication was funded by Fundação Ciência e Tecnologia, IP’s national support through CHRC (UIDP/04923/2020).